Tracking shifts in Atlantic mackerel (Scomber scombrus) larval habitat suitability on the Northeast U.S. Continental Shelf. (19th September 2017) - McManus, M. Conor; Hare, Jonathan A.; Richardson, David E.; Collie, Jeremy S.
Abstract: Climate change has altered the oceanographic environment and subsequently the habitats of marine species. Fish and invertebrate populations' responses to habitat include movement with latitude and depth to remain within their fundamental niches. The northwest Atlantic mackerel ( Scomber scombrus ) population has fluctuated over the last century due in part to changes in the environment. We used species distribution models to understand the influence of the physical (temperature) and biological (zooplankton) environment on mackerel larval abundance, and how such relations have determined larval habitat suitability in the Northeast U.S. Shelf. Atlantic mackerel larval presence and abundance correlated with sea temperature and copepod abundances, suggesting that larval survival may be sensitive to specific temperatures and zooplankton prey. Predicted abundances were spatially interpolated to estimate Atlantic mackerel larval suitable habitat. Metrics for habitat quality indicate that the Mid‐Atlantic Bight has become less suitable over time. Since the 1970s, the proportion of Northeast U.S. Shelf suitable habitat located in the Mid‐Atlantic Bight has decreased, as southern New England and the western Gulf of Maine regions have become more suitable. Habitat suitability within the Northeast U.S. Shelf has shifted northeast: from the Mid‐Atlantic Bight‐southern New England border towards the northeast portion of southern New England. While total Northeast U.S. Shelf habitat suitability has decreased since the 1970s, the decline in the time series trend was not statistically significant. Thus, while select ecoregions have decreased in habitat suitability, larval habitat does not appear to be the only contributor to decreases in the U.S. Atlantic mackerel contingent.